Pengaruh Kecerdasan Emosional Terhadap Kemampuan Penyelesaian Konflik - Ita Sofiana Putri; Farikha Wahyu Lestari; Ismah Ismah (Scidacplus, 2026)
Social interactions have the potential to cause differences or conflicts that give rise to interpersonal conflicts, including in the school environment. Conflict resolution is an important social skill for students to be able to manage differences constructively and maintain harmonious interpersonal relationships. One factor suspected to play a role in an individual's ability to resolve conflicts is emotional intelligence. This study aims to analyze the influence of emotional intelligence on conflict resolution skills in grade X students of SMA Negeri 1 Mranggen, Demak Regency. The study used a quantitative approach with an ex post facto design. The research sample consisted of 188 students, selected through a random sampling technique. Data were collected using a Likert scale questionnaire compiled based on aspects of emotional intelligence according to Goleman (1995) and conflict resolution skills according to Bodine and Crawford (1996). Data analysis was carried out using descriptive statistics, prerequisite tests, Pearson correlation, and simple linear regression with the help of IBM SPSS Statistics 21. The results showed that students' emotional intelligence was in the good category with an average of 73.58%, while their conflict resolution skills were also in the good category with an average of 70.51%. The results of the simple linear regression test also show that emotional intelligence does not have a significant effect on the ability to resolve conflicts, with a coefficient of determination (R²) value of 1.4%, so that other factors outside the research influence 98.6% of the variation in the ability to resolve conflicts.